IKHTILAF ULAMA TENTANG KEDUDUKAN BASMALAH DALAM AL-FATIHAH DIBACA KETIKA SHALAT - FATHURRAHMAN AZHARI (Syariah: Jurnal Hukum dan Pemikiran, 2015)
The authorities agreed when starting an act of worship was told to read Basmalah, but the deviation that the Basmalah including one verse of Surah al-Fatihah, and there are also differences of Basmalah in the prayer that is read when reading Surah al-Fatihah. Imam Malik, Imam Hana?and Ahmad ibn Hanbal agree that Basmalah does not include the verses from Surah al-Fatihah, but they differ in reading in the prayer if Imam Malik argues that is Makruh, and then Imam Hana?and Imam Ahmad bin Hanbal believes it as Sunnat. While the opinion of Imam Sha?'i Basmalah is one of the verses of Surah al-Fatihah, so, we must read Basmalah in the prayer when reading Surah al-Fatihah. Each of the scholars expresses their opinions with arguments of the Sunnah that supports and reinforces his view.